Improving Quality of Character Based Learning through Quality Improvement Management at SDN Sekarmojo III and SDN Purwosari II - Wulandari, Siti Auliyah; Suyanto, Suyanto; Wahyudi, M. Furqon (The Future of Education Journal, 2026)
Character education is a crucial foundation in shaping a quality generation. However, its implementation at the elementary school level is often suboptimal, particularly in terms of structured management. This study aims to describe steps for improving character-based learning quality through quality management in the planning, implementation, and supervision stages at SDN Sekarmojo III and SDN Purwosari II. The research uses a qualitative approach with descriptive methods. Data were collected through observation, in-depth interviews, and documentation, and analyzed interactively through data reduction, data display, and conclusion drawing. The results indicate that implementing quality management integrated with character values can enhance learning quality and develop students' character. The conclusions of this study are expected to serve as a reference for developing character education management in elementary schools.